Changing the Diameter of the Bone Tunnel Is More Effective Than Changing the Tunnel Shape for Restoring Joint Functionality After ACL Reconstruction - Wang, Huizhi; Zhang, Min; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2020)
The clinical implications of changing the shape of the bone tunnel for ACL reconstruction (ACLR) is controversial and few studies have reported on the long-term prevalence for osteoarthritis. As such, this study aims to evaluate the effect of tunnel shape on joint biomechanics. Finite element models of an ACLR were constructed with different shapes (circular, oval, rounded rectangular, rectangular and gourd-shaped) and diameters (7.5, 8.5 and 9.5 mm) for the bone tunnel. A combined loading of 103 N anterior tibial load, 7.5 Nm internal tibial moment and 6.9 Nm valgus tibial moment was applied at a joint flexion angle of 20°. Joint kinematics and the strain energy density (SED) on the articular cartilage were compared among the different groups. The results showed that conventional ACLR (circular tunnel) lead to an increase in joint kinematics over the intact joint, a lower ligament force and a higher SED on the lateral tibial cartilage. ACLR using the other tunnel shapes resulted in even greater joint kinematics, lower graft force and greater SED on the lateral tibial cartilage. Increasing the tunnel diameter better restored joint kinematics, graft force and articular SED, bringing these values closer to those from the intact knee. In conclusion, increasing the tunnel diameter may be more effective than changing the tunnel shape for restoring joint functionality after ACLR.